Computation of interfacial flows using Continuous Surface Stress method with adaptive mesh refinement in a quad/octree grid structure. (15th September 2022) - Liu, M.; Bothe, D.; Yang, Yiren; Chen, Hao
Abstract: A new implementation of the Continuous Surface Stress (CSS) method into a quad/octree grid structure is presented, which realizes effective adaptive mesh refinement (AMR) for computation of interfacial flows with significant topology changes. The momentum conservation property of the CSS method is exactly retained. The extension of the CSS method to the AMR framework and a designed phase-based refinement criterion are described in detail. The new implementation works on 2D/3D and on axis-symmetric grids. The proposed method is shown to be accurate in the computation of the Laplace pressure. The spurious velocity is evaluated based on the benchmark cases of static droplet and translating droplet. The test case of multiple droplets colliding onto a liquid film illustrates the functionality and efficiency of the method in dealing with complex interfacial flows. Thanks to the high resolution realized by AMR, it is shown in computation of the process of binary droplet collisions that the method is capable of capturing finest interfacial structures subjected to complex topology changes. Highlights: Momentum conservation property of the CSS method exactly retained. Computation of multiple droplets impact onto a liquid film by a single work station. Finest interfacial structures captured within collision complex.